Lipids for CD8+ TILs: Beneficial or harmful? - Wu, Duojiao; Chen, Yuwen (Frontiers in Immunology, 2022)
Lipids and lipid metabolism play crucial roles in regulating T cell function and are tightly related to the establishment of immune memory. It is reported that tumor-infiltrating CD8+T lymphocytes (CD8+TILs) burn fats to restore their impaired effector function due to the lack of glucose. Conversely, fatty acids (FAs) and cholesterols in the tumor microenvironment drive the CD8+ TILs dysfunction. The origin of dysfunctional CD8+ TILs shares important features with memory T cell’s precursor, but whether lipids and/or lipid metabolism reprogramming directly influence the memory plasticity of dysfunctional CD8+ TILs remains elusive. It is necessary to understand the interplay between cellular lipid metabolism and dysfunction of CD8+ TILs in the case of targeting T cell’s metabolism to synergize cancer immunotherapy. Therefore, in this review, we summarize the latest research on CD8+ TILs lipid metabolism, evaluate the impacts of lipids in the TME to CD8+ TILs, and highlight the significance of promoting memory phenotype cell formation by targeting CD8+ T cells lipid metabolism to provide longer duration of cancer immunotherapy efficacy.